HPLC sugar profiles of Malaysian honeys - Ibrahim, Nurul Husna Qaiyimah (2015)
Sugar profiles of 34 honey samples from different regions of Malaysia which coming from Perlis, Kedah, Kelantan, Perak, Terengganu, Kuala Lumpur, Selangor, Pahang, Melaka, Negeri Sembilan, Johor, Sabah and Sarawak are analysed by HPLC with UV detector at 195 nm. These samples consist of 10 Kelulut honeys, 2 Acacia honeys, 3 Hutan honeys, 9 Tualang honeys and 10 unknown honeys (unknown types). Five sugars are identified which are three monosaccharides and two dissacharides. Fructose (32.66±1.19%) is the major sugar in all samples followed by glucose (31.57±1.20%), galactose (2.62±1.94%), maltose (2.06±0.35%) and sucrose (2.95±0.39%). Fructose and glucose are the main monosaccharides in all samples. Galactose, sucrose and maltose are only present in certain honey samples. Hierarchical clustering analysis (HCA) and principal component analysis (PCA) used to classify honeys correctly based on sugar composition. Euclidean distance shows the concentration of each sugars presence in the samples which differentiate low and high concentration of total sugar. Cosine distance study recognized the pattern of sugar in honey samples from different region of Malaysia. Based on principal component analysis (PCA), honey samples are scattered according to their PC1 and PC2, thus allows the authenticity prediction.